Nanometer coating with high radiation heat exchange capability and preparation method thereof
By introducing homemade modified silica mixed suspension and modified graphene oxide in high-radiation nanocoatings, the problems of low density and complex construction process of coatings in high-temperature kilns are solved, and efficient and stable coating performance and simplified construction process are achieved.
Patent Information
- Application Number
- CN202411727562.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
When existing high-radiation nanocoatings are used in high-temperature kilns, the bonding density between the coating and the substrate is low, and cannot be stable in severe temperature fluctuations. The construction process is complex, which affects production efficiency and cost.
Nanocoatings are prepared by mechanical stirring and sonication methods such as homemade modified silica mixed suspension and modified graphene oxide, so as to improve the temperature resistance and adhesion of the coating.
The coating is maintained at high temperatures, improved thermal shock resistance and adhesion, simplified construction technology, improved production efficiency and reduced time costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano coatings, and specifically relates to a nano coating with high radiation heat exchange capacity and a preparation method thereof. Background Art
[0002] High temperature kilns are key equipment for industrial heating and are widely used in various industries. For example, high temperature kilns are needed in pillar industries of the national economy such as cement, power generation, glass, metallurgy, and chemical industry.
[0003] At the same time, high-temperature kilns are high-energy consumption equipment. The annual energy consumption of about 120,000 high-temperature kilns in my country is at least 260 million tons of standard coal, accounting for 30% of my country's total energy consumption and 60% of industrial energy consumption. Energy conservation of industrial high-temperature kilns in my country is an urgent issue. Properly solving this problem is also an urgent need to accelerate the transformation of economic development mode. It also means that the energy conservation of industrial high-temperature kilns has huge room for improvement, and the research and development of energy-saving technologies will also become a key area.
[0004] Among them, relevant energy-saving measures have also been developed for industrial high-temperature kilns, which are large energy consumers. These measures mainly revolve around the heating process, insulation process and waste heat utilization process of the kiln.
[0005] Infrared radiation material (or high radiation material) is a new type of material produced with the development of infrared radiation technology research. It is a new type of functional material with a wide range of uses. With the rapid development of infrared technology, high radiation materials are more and more widely used in industry. By utilizing the high heat absorption and high emission properties of special materials, a large amount of infrared rays are emitted while absorbing heat to act on the heated object. This material can make high use of the heat of the inner wall of the furnace and return it to the inside of the kiln, increasing the thermal efficiency of the kiln. While saving energy, it also effectively protects the inner wall of the kiln and extends the service life of the kiln.
[0006] There are generally two methods for using high-radiation materials: integral pressing and sintering molding and paint brushing. Among them, the integral pressing and sintering molding method cannot produce irregular, large-area integral products due to size limitations; and the paint brushing method has become the main application method of high-radiation materials because of its simple and convenient process and low cost.
[0007] The prior art includes, for example, the Chinese invention patent with application number CN202211689496.9, which discloses a nano coating with high radiation heat exchange capacity and a construction method, wherein the construction method is as follows: step 1, caulking or polishing the surface of the object to be sprayed to make it as smooth as possible; step 2, mixing the nano coating of the first aspect of the present invention according to parts by weight, stirring evenly and then spraying; step 3, raising the ambient temperature of the sprayed object in three stages; The three-stage step-by-step heating includes raising the temperature to 200°C and maintaining it for 2 hours; then raising the temperature to 500°C and maintaining it for 3 hours; and finally raising the temperature to 850°C and maintaining it for 4 hours. Furthermore, in step 2, the spraying is performed 2 to 3 times.
[0008] The defect is that the close bonding between the coating and the substrate is achieved through multiple spraying processes, and the temperature fluctuations in high-temperature kilns used for industrial heating are usually more severe. The coating that has been sprayed multiple times cannot remain stable in frequent thermal cycles and has high requirements on the construction process. Multiple spraying operations will also affect the overall production efficiency and increase time costs.
[0009] The above-mentioned existing technologies do not improve the performance of the coating itself, and there is still room for optimization and improvement in heat exchange capacity, thermal shock resistance, etc.
[0010] Therefore, there is an urgent need to introduce new process technologies to solve the above problems and seek more feasible solutions. Summary of the invention
[0011] In order to solve the defects existing in the above technical scheme, the purpose of the present invention is to provide a nano coating with high radiation heat exchange capacity and a preparation method; the purpose of the present invention can be achieved by the following technical scheme: a nano coating with high radiation heat exchange capacity, which is composed of the following parts by weight: 10-15 parts of cordierite micropowder, 4-8 parts of ferric oxide, 5-10 parts of silicon carbide, 5-10 parts of chromium oxide, 3-8 parts of titanium dioxide, 5-10 parts of aluminum oxide, 1-5 parts of nickel oxide, 8-12 parts of homemade modified silicon dioxide mixed suspension, 18-28 parts of composite binder, 0.4-1.2 parts of dispersant, 0.1-0.2 parts of defoaming agent, 0.3-0.5 parts of leveling agent, and 12-22 parts of deionized water.
[0012] The particle size of the cordierite powder is less than 5 μm; The particle sizes of the ferric oxide and chromium oxide are both between 50-150 nm; The particle sizes of silicon carbide, titanium dioxide, aluminum oxide and nickel oxide are all between 100 and 500 nm; The composite binder is a mixture obtained by uniformly mixing phosphate and high-temperature cement in a mass ratio of 1:1.
[0013] Further, the phosphate is one of sodium phosphate and sodium dihydrogen phosphate; Furthermore, the grade of the high temperature mortar is YJF-2, which is purchased from Henan Sun Hung Kai Refractory Materials Co., Ltd.; the maximum operating temperature is 1500 degrees Celsius.
[0014] The method for preparing the homemade modified silicon dioxide mixed suspension comprises the following steps: adding silicon dioxide powder and N-imidazolepropyltrimethoxysilane to a 75% ethanol aqueous solution, and ultrasonically treating the solution for 2 hours, thereby preparing N-imidazolepropyltrimethoxysilane-modified silicon dioxide; centrifuging the suspension for 3 times at a speed of 500 rpm, and washing away the unreacted N-imidazolepropyltrimethoxysilane with a 75% ethanol aqueous solution, collecting the N-imidazolepropyltrimethoxysilane-modified silicon dioxide at the bottom of a centrifuge tube, and redispersing the mixture in a 75% ethanol aqueous solution, thereby preparing modified silicon dioxide; and subsequently adding modified graphene oxide to the solution, and simultaneously stirring and ultrasonically treating the solution for 4 hours, thereby preparing a homemade modified silicon dioxide mixed suspension bonded by hydrogen bonds.
[0015] Preparation of the modified graphene oxide: graphene oxide is taken and placed in a 75% ethanol aqueous solution for full dispersion, and then after ultrasonic treatment for 2 hours, hexadecyltrimethoxysilane is added, and then the mixed solution is continuously stirred and ultrasonically treated for 2 hours, and then the suspension is centrifuged at a speed of 500 rpm for 3 times, and the unreacted hexadecyltrimethoxysilane is washed away with a 75% ethanol aqueous solution, and finally the modified graphene oxide is collected as a solid mass at the bottom of the centrifuge tube, that is, the surface modification of the graphene oxide is completed, and the modified graphene oxide is prepared.
[0016] A method for preparing a nano coating with high radiation heat exchange capacity: cordierite powder is added to a composite binder, mechanically stirred for 30 minutes, and after being stirred evenly, ferric oxide, silicon carbide, chromium oxide, titanium dioxide, aluminum oxide, nickel oxide, and modified silicon dioxide are added in sequence to preliminarily prepare a mixture A; deionized water is then added to the mixture A, mechanically stirred for 30-45 minutes, and finally a dispersant, a defoaming agent, and a leveling agent are added in sequence, and stirred evenly to prepare a nano coating with high radiation heat exchange capacity.
[0017] Furthermore, in specific applications, the uniformly stirred nano coating can be subjected to ball milling treatment using a planetary ball mill with a ball milling speed of 600-800 r / min and a ball milling time of 1-2 h.
[0018] Furthermore, the dispersant is one of AFCONA-5009 and FLUIJET 1720; the dispersants are purchased from Shanghai Yuanhe Chemical Co., Ltd.; Furthermore, the defoamer is a polyether defoamer TEGO Antifoam 3062; the defoamer is purchased from Evonik Digo Chemical Co., Ltd.; Furthermore, the leveling agent is one or both of AFCONA-3085 and AFCONA-3587; the leveling agent is purchased from Efcona Polymer Co., Ltd.
[0019] Preparation of modified graphene oxide: 0.1 g of graphene oxide was taken and placed in 80 ml of 75% ethanol aqueous solution for full dispersion. After 2 h of ultrasonic treatment, 0.8 g of hexadecyltrimethoxysilane was added, and the mixed solution was continuously stirred and ultrasonically treated for 2 h. The suspension was then centrifuged at 500 rpm for 3 times, and the unreacted hexadecyltrimethoxysilane was washed away with 75% ethanol aqueous solution. Finally, the modified graphene oxide was collected as a solid mass at the bottom of the centrifuge tube, thereby completing the surface modification of the graphene oxide and preparing the modified graphene oxide.
[0020] A method for preparing a homemade modified silica mixed suspension: 30 g of silica powder and 2 g of N-imidazolepropyltrimethoxysilane are added to 80 ml of 75% ethanol aqueous solution, and ultrasonically treated for 2 hours to prepare N-imidazolepropyltrimethoxysilane-modified silica; the suspension is centrifuged three times at a speed of 500 rpm, and the unreacted N-imidazolepropyltrimethoxysilane is washed away with 75% ethanol aqueous solution, the N-imidazolepropyltrimethoxysilane-modified silica is collected at the bottom of the centrifuge tube, and redispersed in 40 ml of 75% ethanol aqueous solution to prepare modified silica; then modified graphene oxide is added to the solution, and stirring and ultrasonic treatment are performed for 4 hours to prepare a homemade modified silica mixed suspension bonded by hydrogen bonds.
[0021] Furthermore, the coating adopts a step-by-step sintering and curing process. After coating, the temperature is first raised to 100 degrees Celsius and maintained for 4 hours, then raised to 200 degrees Celsius and maintained for 2 hours; then raised to 600 degrees Celsius and maintained for 4 hours, and finally raised to 1000 degrees Celsius and maintained for 2 hours; finally, the coating is cooled in the furnace, i.e., sintering and curing are completed, and the preparation of the coating is completed.
[0022] The present invention has the beneficial effects: 1. The present application introduces a self-made modified silica mixed suspension into the nano coating. The imidazole rigid group with large steric hindrance introduced by the modified silica can reduce the mobility of each chain segment in the coating under high temperature environment, thereby further improving the temperature resistance of the coating; and the hexadecyltrimethoxysilane-modified graphene oxide with a long chain structure can improve the adhesion between the coating and the substrate, so that it can remain stable at high temperatures or in situations where the temperature changes drastically, thereby having excellent thermal shock resistance; 2. The self-made modified silica mixed suspension introduced in this application, the two work together, and when added to the coating, not only can the thermal stability and high temperature resistance of the coating be improved, but also a good chemical bond can be formed between the coating matrix, so that the adhesion to the substrate is significantly improved, and the interface bonding performance is improved, so that the coating of this application can be sprayed once, and the surface structure of the cured coating can be more dense and the mechanical properties can be more excellent; 3. The coating of the present application can be sprayed in one time when used in a high-temperature kiln, which is easier to use, greatly improves production efficiency, and reduces the time cost during application. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment, and the illustrative embodiments of the present invention and its description are only used to explain the present invention, and are not used as limitation of the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper limit and the lower limit of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper limit and lower limit of these smaller ranges can be independently included or excluded in the scope.
[0024] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0025] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0026] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0027] The "parts" indicated in the following examples are all parts by weight.
[0028] Example 1 A nano coating with high radiation heat exchange capacity, the components of which are as follows, by weight: 10 parts of cordierite micropowder, 4 parts of ferric oxide, 5 parts of silicon carbide, 5 parts of chromium oxide, 3 parts of titanium dioxide, 5 parts of aluminum oxide, 1 part of nickel oxide, 8 parts of homemade modified silicon dioxide mixed suspension, 18 parts of composite binder, 0.4 parts of dispersant, 0.1 parts of defoamer, 0.3 parts of leveling agent, and 14 parts of deionized water; The particle size of the cordierite powder is less than 5 μm; The particle sizes of the ferric oxide and chromium oxide are both between 50-150 nm; The particle sizes of silicon carbide, titanium dioxide, aluminum oxide and nickel oxide are all between 100 and 500 nm; The composite binder is a mixture of phosphate and high temperature cement mixed in a mass ratio of 1:1; The phosphate is sodium phosphate; The grade of the high temperature mortar is YJF-2, which is purchased from Henan Sun Hung Kai Refractory Materials Co., Ltd. The dispersant is AFCONA-5009; The defoamer is polyether defoamer TEGO Antifoam 3062; The leveling agent is AFCONA-3085.
[0029] A method for preparing a homemade modified silica mixed suspension: 30 g of silica powder and 2 g of N-imidazolepropyltrimethoxysilane are added to 80 ml of 75% ethanol aqueous solution, and ultrasonically treated for 2 hours to prepare N-imidazolepropyltrimethoxysilane-modified silica; the suspension is centrifuged three times at a speed of 500 rpm, and the unreacted N-imidazolepropyltrimethoxysilane is washed away with 75% ethanol aqueous solution, the N-imidazolepropyltrimethoxysilane-modified silica is collected at the bottom of the centrifuge tube, and redispersed in 40 ml of 75% ethanol aqueous solution to prepare modified silica; then modified graphene oxide is added to the solution, and stirring and ultrasonic treatment are performed for 4 hours to prepare a homemade modified silica mixed suspension bonded by hydrogen bonds.
[0030] Preparation of modified graphene oxide: 0.1 g of graphene oxide was taken and placed in 80 ml of 75% ethanol aqueous solution for full dispersion. After 2 h of ultrasonic treatment, 0.8 g of hexadecyltrimethoxysilane was added, and the mixed solution was continuously stirred and ultrasonically treated for 2 h. The suspension was then centrifuged at 500 rpm for 3 times, and the unreacted hexadecyltrimethoxysilane was washed away with 75% ethanol aqueous solution. Finally, the modified graphene oxide was collected as a solid mass at the bottom of the centrifuge tube, thereby completing the surface modification of the graphene oxide and preparing the modified graphene oxide.
[0031] A method for preparing a nano coating with high radiation heat exchange capacity: cordierite powder is added to a composite binder, mechanically stirred for 30 minutes, and after being stirred evenly, 4 parts of ferric oxide, 5 parts of silicon carbide, 5 parts of chromium oxide, 3 parts of titanium dioxide, 5 parts of aluminum oxide, 1 part of nickel oxide, and 8 parts of modified silicon dioxide are added in sequence to preliminarily prepare a mixture A; then deionized water is added to the mixture A, mechanically stirred for 30-45 minutes, and finally a dispersant, a defoaming agent, and a leveling agent are added in sequence, and stirred evenly to prepare a nano coating with high radiation heat exchange capacity.
[0032] In specific applications, the uniformly stirred nano coating can be subjected to ball milling treatment using a planetary ball mill with a ball milling speed of 600-800 r / min and a ball milling time of 1-2 h.
[0033] Example 2 A nano coating with high radiation heat exchange capacity, the components of which are as follows, by weight: 12 parts of cordierite powder, 5 parts of ferric oxide, 7 parts of silicon carbide, 6 parts of chromium oxide, 4 parts of titanium dioxide, 6 parts of aluminum oxide, 2 parts of nickel oxide, 9 parts of self-made modified silicon dioxide mixed suspension, 20 parts of composite binder, 0.6 parts of dispersant, 0.1 parts of defoamer, 0.4 parts of leveling agent, and 14 parts of deionized water; The composite binder is a mixture of phosphate and high temperature cement mixed in a mass ratio of 1:1; The phosphate is sodium dihydrogen phosphate; The grade of the high temperature mortar is YJF-2, which is purchased from Henan Sun Hung Kai Refractory Materials Co., Ltd. The dispersant is FLUIJET 1720; The defoamer is polyether defoamer TEGO Antifoam 3062; The leveling agent is AFCONA-3587; Among them, in Example 2, the preparation method of the homemade modified silica mixed suspension and the preparation method of the nano coating with high radiation heat exchange capacity are consistent with those in Example 1.
[0034] Example 3 A nano coating with high radiation heat exchange capacity, the components of which are as follows, by weight: 14 parts of cordierite powder, 6 parts of ferric oxide, 8 parts of silicon carbide, 8 parts of chromium oxide, 6 parts of titanium dioxide, 8 parts of aluminum oxide, 4 parts of nickel oxide, 10 parts of a self-made modified silicon dioxide mixed suspension, 24 parts of a composite binder, 0.8 parts of a dispersant, 0.2 parts of a defoamer, 0.4 parts of a leveling agent, and 16 parts of deionized water; The composite binder is a mixture of phosphate and high temperature cement mixed in a mass ratio of 1:1; The phosphate is sodium dihydrogen phosphate; The grade of the high temperature mortar is YJF-2, which is purchased from Henan Sun Hung Kai Refractory Materials Co., Ltd. The dispersant is AFCONA-5009; The defoamer is polyether defoamer TEGO Antifoam 3062; The leveling agent is AFCONA-3085; Among them, in Example 3, the preparation method of the homemade modified silica mixed suspension and the preparation method of the nano coating with high radiation heat exchange capacity are consistent with those in Example 1.
[0035] Example 4 A nano coating with high radiation heat exchange capacity, the components of which are as follows by weight: 14 parts of cordierite powder, 7 parts of ferric oxide, 9 parts of silicon carbide, 9 parts of chromium oxide, 7 parts of titanium dioxide, 9 parts of aluminum oxide, 4 parts of nickel oxide, 11 parts of homemade modified silicon dioxide mixed suspension, 26 parts of composite binder, 1 part of dispersant, 0.2 parts of defoamer, 0.5 parts of leveling agent, and 19 parts of deionized water; The composite binder is a mixture of phosphate and high temperature cement mixed in a mass ratio of 1:1; The phosphate is sodium phosphate; The grade of the high temperature mortar is YJF-2, which is purchased from Henan Sun Hung Kai Refractory Materials Co., Ltd. The dispersant is one of FLUIJET 1720; The defoamer is polyether defoamer TEGO Antifoam 3062; The leveling agent is AFCONA-3587; Among them, in Example 4, the preparation method of the homemade modified silica mixed suspension and the preparation method of the nano coating with high radiation heat exchange capacity are consistent with those in Example 1.
[0036] Example 5 A nano coating with high radiation heat exchange capacity, the components of which are as follows by weight: 15 parts of cordierite powder, 8 parts of ferric oxide, 10 parts of silicon carbide, 10 parts of chromium oxide, 8 parts of titanium dioxide, 10 parts of aluminum oxide, 5 parts of nickel oxide, 12 parts of a self-made modified silicon dioxide mixed suspension, 28 parts of a composite binder, 1.2 parts of a dispersant, 0.2 parts of a defoamer, 0.5 parts of a leveling agent, and 22 parts of deionized water; The composite binder is a mixture of phosphate and high temperature cement mixed in a mass ratio of 1:1; The phosphate is sodium dihydrogen phosphate; The grade of the high temperature mortar is YJF-2, which is purchased from Henan Sun Hung Kai Refractory Materials Co., Ltd. The dispersant is FLUIJET 1720; The defoamer is polyether defoamer TEGO Antifoam 3062; The leveling agent is AFCONA-3587; Among them, in Example 5, the preparation method of the homemade modified silica mixed suspension and the preparation method of the nano coating with high radiation heat exchange capacity are consistent with those in Example 1.
[0037] Comparative Example 1 A nano coating with high radiation heat exchange capacity, the components of which are as follows, by weight: 14 parts of cordierite powder, 6 parts of ferric oxide, 8 parts of silicon carbide, 8 parts of chromium oxide, 6 parts of titanium dioxide, 8 parts of aluminum oxide, 4 parts of nickel oxide, 10 parts of modified silicon dioxide, 24 parts of composite binder, 0.8 parts of dispersant, 0.2 parts of defoamer, 0.4 parts of leveling agent, and 16 parts of deionized water; Preparation method of modified silica: 30g of silica powder and 2g of N-imidazolepropyltrimethoxysilane are added to 80ml of 75% ethanol aqueous solution, and ultrasonically treated for 2h to prepare N-imidazolepropyltrimethoxysilane modified silica; the suspension is centrifuged 3 times at a speed of 500 rpm, and the unreacted N-imidazolepropyltrimethoxysilane is washed away with 75% ethanol aqueous solution, and the N-imidazolepropyltrimethoxysilane modified silica is collected at the bottom of the centrifuge tube, and redispersed in 40ml of 75% ethanol aqueous solution to prepare modified silica.
[0038] Among them, in Comparative Example 1, except that the preparation method of modified silicon dioxide is different from that of Example 3, the remaining components and the preparation method of the nano coating with high radiation heat exchange capacity are consistent with those of Example 3.
[0039] Comparative Example 2 A nano coating with high radiation heat exchange capacity, the components of which are as follows, measured by weight: 14 parts of cordierite micropowder, 6 parts of ferric oxide, 8 parts of silicon carbide, 8 parts of chromium oxide, 6 parts of titanium dioxide, 8 parts of aluminum oxide, 4 parts of nickel oxide, 10 parts of a mixed suspension of silicon dioxide and graphene oxide, 24 parts of a composite binder, 0.8 parts of a dispersant, 0.2 parts of a defoaming agent, 0.4 parts of a leveling agent, and 16 parts of deionized water.
[0040] The preparation method of the silica-graphene oxide mixed suspension is as follows: 30 g of silica powder is added to 80 ml of 75% ethanol aqueous solution, and ultrasonically treated for 2 hours, and then graphene oxide is added, and stirring and ultrasonically treated for 4 hours are performed to prepare the silica-graphene oxide mixed suspension.
[0041] Among them, in Comparative Example 2, silicon dioxide and graphene oxide have not undergone any chemical modification, and the remaining components and the preparation method of the nano-coating with high radiation heat exchange capacity are consistent with those in Example 3.
[0042] Comparative Example 3 A nano coating with high radiation heat exchange capacity, the components of which are as follows, by weight: 14 parts of cordierite powder, 6 parts of ferric oxide, 8 parts of silicon carbide, 8 parts of chromium oxide, 6 parts of titanium dioxide, 8 parts of aluminum oxide, 4 parts of nickel oxide, 10 parts of KH550 modified silicon dioxide mixed suspension, 24 parts of composite binder, 0.8 parts of dispersant, 0.2 parts of defoamer, 0.4 parts of leveling agent, and 16 parts of deionized water; Preparation of modified graphene oxide: 0.1 g of graphene oxide was taken and placed in 80 ml of 75% ethanol aqueous solution for full dispersion. After 2 h of ultrasonic treatment, 0.8 g of hexadecyltrimethoxysilane was added, and the mixed solution was continuously stirred and ultrasonically treated for 2 h. The suspension was then centrifuged at 500 rpm for 3 times, and the unreacted hexadecyltrimethoxysilane was washed away with 75% ethanol aqueous solution. Finally, the modified graphene oxide was collected as a solid mass at the bottom of the centrifuge tube, thereby completing the surface modification of the graphene oxide and preparing the modified graphene oxide.
[0043] A method for preparing a homemade modified silica mixed suspension: 30 g of silica powder and 2 g of KH550 are added to 80 ml of 75% ethanol aqueous solution, and ultrasonically treated for 2 hours to prepare KH550 modified silica; the suspension is centrifuged three times at a speed of 500 rpm, and the unreacted KH550 is washed away with 75% ethanol aqueous solution, the KH550 modified silica is collected at the bottom of the centrifuge tube, and redispersed in 40 ml of 75% ethanol aqueous solution to prepare modified silica; then modified graphene oxide is added to the solution, and stirring and ultrasonic treatment are carried out for 4 hours to prepare a KH550 modified silica mixed suspension.
[0044] Among them, in Comparative Example 3, except that the preparation method of the KH550 modified silica mixed suspension is different from that of Example 3, the remaining components and the preparation method of the nano coating with high radiation heat exchange capacity are consistent with those of Example 3.
[0045] Test example During the test, Examples 1-5 and Comparative Examples 1-3 all adopted a step-by-step sintering and curing process. After coating, the temperature was first raised to 100 degrees Celsius and maintained for 4 hours, then raised to 200 degrees Celsius and maintained for 2 hours; then raised to 600 degrees Celsius and maintained for 4 hours, and finally raised to 1000 degrees Celsius and maintained for 2 hours; finally, the coating was cooled in the furnace, that is, the sintering and curing were completed, and the preparation of the coating was completed; specifically, during the test, the thickness of the cured coating was controlled at 1 mm.
[0046] Thermal shock resistance test: The protective coating prepared by the nano-coating with high radiation heat exchange capacity prepared in Examples 1-5 and Comparative Examples 1-3 was placed in a high-temperature muffle furnace and heated to 1100 degrees Celsius, and kept at this temperature for 10 minutes, then taken out and air-cooled. Cooling to room temperature is one thermal cycle. The number of thermal cycles when cracks begin to appear on the coating is recorded; Emissivity test: In thermal equilibrium, Kirchhoff's law is used to calculate the emissivity of the substrate after the protective coating is applied; Adhesion test: With reference to the national standard GB / T 9286-2021 "Scratch test for paint and varnish", the adhesion test of the protective coating was completed; the test results are shown in Table 1 below: Table 1 Comprehensive performance analysis: The unmodified silicon dioxide and graphene oxide used in Comparative Example 2 have the highest Since silicon dioxide and graphene oxide have strong hydrophilicity and surface polarity, especially graphene oxide with carboxyl and hydroxyl groups on the surface, they are easy to agglomerate and difficult to disperse in the coating; and the surface energy of both is high, and the compatibility with other substrates in the coating is poor, so that the prepared coating cannot be well combined with the substrate, so that its adhesion is poor and its thermal shock resistance is also poor. Comparative Example 1 does not incorporate modified graphene oxide, but only uses modified silicon dioxide, which does not incorporate modified graphene oxide with a long chain structure. Although its adhesion is not as good as that of Comparative Example 3, it is also significantly better than Comparative Example 2.
[0047] Comparative Example 3 uses the commonly used KH550 modified silica. Although its adhesion is stronger than that of Comparative Example 2, it still has a certain gap with Examples 1-5. The possible reason is that the imidazole rigid group with large steric hindrance introduced by the modified silica in Examples 1-5 can reduce the mobility of each chain segment in the coating under high temperature environment, thereby improving the temperature resistance of the coating; and the homemade modified silica mixed suspension introduced in Examples 1-5, the two work together, and are added to the coating, which can not only improve the thermal stability and high temperature resistance of the coating, but also form a good chemical bond with the coating matrix, so that the adhesion to the substrate is significantly improved, and the interface bonding performance is improved. The hexadecyltrimethoxysilane-modified graphene oxide with a long chain structure can improve the adhesion between the coating and the substrate, and only the synergistic effect of the two can make the coating reach level 0 adhesion, so that it can remain stable at high temperatures or in situations where the temperature changes drastically, thereby having excellent thermal shock resistance.
[0048] The coating of the present application can be sprayed in one time when used in a high-temperature kiln, is easier to use, greatly improves production efficiency, and reduces the time cost of application. At the same time, the surface structure of the cured coating is denser and the mechanical properties are better.
[0049] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A nano coating with high radiation heat transfer capacity, characterized in that: The composition is as follows, by weight, including: 10-15 parts of cordierite powder, 4-8 parts of ferric oxide, 5-10 parts of silicon carbide, 5-10 parts of chromium oxide, 3-8 parts of titanium dioxide, 5-10 parts of aluminum oxide, 1-5 parts of nickel oxide, 8-12 parts of homemade modified silicon dioxide mixed suspension, 18-28 parts of composite binder, 0.4-1.2 parts of dispersant, 0.1-0.2 parts of defoaming agent, 0.3-0.5 parts of leveling agent, and 12-22 parts of deionized water.
2. The nano coating with high radiation heat exchange capacity according to claim 1, characterized in that: In terms of weight, the composition is as follows: 14 parts of cordierite powder, 6 parts of ferric oxide, 8 parts of silicon carbide, 8 parts of chromium oxide, 6 parts of titanium dioxide, 8 parts of aluminum oxide, 4 parts of nickel oxide, 10 parts of homemade modified silicon dioxide mixed suspension, 24 parts of composite binder, 0.8 parts of dispersant, 0.2 parts of defoaming agent, 0.4 parts of leveling agent, and 16 parts of deionized water.
3. The nano coating with high radiation heat exchange capacity according to claim 1, characterized in that: The particle size of the cordierite powder is less than 5 μm.
4. The nano coating with high radiation heat exchange capacity according to claim 1, characterized in that: The particle sizes of the ferric oxide and chromium oxide are both between 50 and 150 nm.
5. The nano coating with high radiation heat exchange capacity according to claim 1, characterized in that: The particle sizes of silicon carbide, titanium dioxide, aluminum oxide and nickel oxide are all between 100 and 500 nm.
6. The nano coating with high radiation heat exchange capacity according to claim 1, characterized in that: The composite binder is a mixture of phosphate and high temperature cement mixed in a mass ratio of 1:1; The phosphate is one of sodium phosphate and sodium dihydrogen phosphate.
7. The nano coating with high radiation heat exchange capacity according to claim 1, characterized in that: The method for preparing the homemade modified silicon dioxide mixed suspension comprises the following steps: adding silicon dioxide powder and N-imidazolepropyltrimethoxysilane to a 75% ethanol aqueous solution, and ultrasonically treating the solution for 2 hours, thereby preparing N-imidazolepropyltrimethoxysilane-modified silicon dioxide; centrifuging the suspension for 3 times at a speed of 500 rpm, and washing away the unreacted N-imidazolepropyltrimethoxysilane with a 75% ethanol aqueous solution, collecting the N-imidazolepropyltrimethoxysilane-modified silicon dioxide at the bottom of a centrifuge tube, and redispersing the mixture in a 75% ethanol aqueous solution, thereby preparing modified silicon dioxide; and subsequently adding modified graphene oxide to the solution, and simultaneously stirring and ultrasonically treating the solution for 4 hours, thereby preparing a homemade modified silicon dioxide mixed suspension bonded by hydrogen bonds.
8. The nano coating with high radiation heat exchange capacity according to claim 7, characterized in that: The preparation method of the modified graphene oxide is as follows: taking graphene oxide, placing it in a 75% ethanol aqueous solution to fully disperse it, then after ultrasonic treatment for 2 hours, adding hexadecyltrimethoxysilane, then continuously stirring and ultrasonically treating the mixed solution for 2 hours, then centrifuging the suspension at a speed of 500 rpm for 3 times, and washing away the unreacted hexadecyltrimethoxysilane with a 75% ethanol aqueous solution, and finally collecting the modified graphene oxide as a solid mass at the bottom of a centrifuge tube, that is, completing the surface modification of the graphene oxide, and preparing the modified graphene oxide.
9. A nano coating with high radiation heat exchange capacity as claimed in any one of claims 1 to 8, characterized in that: The preparation method of the nano coating with high radiation heat exchange capacity comprises the following steps: adding cordierite powder to a composite binder, mechanically stirring for 30 minutes, and after stirring evenly, sequentially adding ferric oxide, silicon carbide, chromium oxide, titanium dioxide, aluminum oxide, nickel oxide, and modified silicon dioxide to preliminarily prepare a mixture A; then, adding deionized water to the mixture A, mechanically stirring for 30-45 minutes, and finally sequentially adding a dispersant, a defoaming agent, and a leveling agent, and stirring evenly to prepare a nano coating with high radiation heat exchange capacity.
10. The nano coating with high radiation heat exchange capacity according to claim 9, characterized in that: The method for preparing the nano coating with high radiation heat exchange capacity can be used to prepare the nano coating with high radiation heat exchange capacity using a planetary ball mill at a ball milling speed of 600-800 r / min and a ball milling time of 1-2 h.
Citation Information
Patent Citations
Nanometer coating with high radiation heat exchange capacity and construction method
CN115772363A
Ceramic coating film composite and preparation method thereof
CN102061126A
High-temperature infrared energy-saving coating based on boride ceramics and preparation method thereof
CN103937301A
Graphene infrared heat radiation coating and preparation method thereof
CN106085104A
Inorganic modified high-temperature-resistant high-emissivity graphene coating and preparation method thereof
CN109880408A